Экстракционно-фотометрическое определение бензилпенициллина красителем тиазинового ряда триметилтионином - Н. О. Геокчян (Հայաստանի ԳԱԱ)
Բենզիլպենիցիլինի և եռմեթիլթիոնինի փոխազդեցությունից առաջացած միությունը (իոնական ասոցիատը) լուծահանելու համար լավագույն էքստրագենտ է ընտրվել դիքլորէթանը, որն էլ ապահովում է իոնական ասոցիատի էքստրակտի օպտիկական խտության մաք սիմալ արժեք, իսկ “կույր” էքստրակտի` համեմատաբար մինիմալ ար ժեք: Մաքսիմում լուսակլանում դիտվում է λ=655 նմ ալիքի երկարու թյան տակ: Ջրային ֆազի օպտիմալ թթվայնության մարզը ընկնում է pH – 5,7–5,8 թորած ջրում: Interaction of benzilpenicillinum anion with thiazin raw has been studied.Compound forming in the system is extracted by dichloretane. Maximal light absorbance (extinction) for extracts forming compound as well as for “blind”extracts is observed at 655 nm wavelength. At the optimal acidity conditions(pH – 5,7–5,8) benzilpenicillinum is extracted almost quantitatively (R=96) to the organic solvent phase by means of single extraction during 1 minutes shaking. The range of determined concentration of benzilpenicillinum is 5,0– 360 mkg/ml. The molar coefficient of extinction is 655 110e = 0 l, mol-1, cm-1.
Keywords: Medicine; Other systems of medicine